PENGARUH TERPAAN INFORMASI PANDEMI COVID-19 TERHADAP LOYALITAS WISATAWAN BERWISATA DENGAN MINAT BERKUNJUNG SEBAGAI VARIABEL MEDIASI - I Made Trisna Semara; Denok Lestari (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
This study discusses the role of the media in conveying information which changes the perceptions, attitudes, and behavior of the audiences. National TV, mass media, and electronic media provide information on the spread of COVID-19 nationwide every day, thus giving a negative impact on tourism development. The tourists do not dare to move out of the area or even travel. This explains that the media can influence the interest of tourists to travel. On the other hand, information media related to COVID-19 aims to handle the spread of COVID-19 optimally. However, since the news of COVID-19, tourists are afraid to move or travel. Loyalty of tourists traveling has decreased. The purpose of this study was to determine the relationship between exposure to information on the COVID-19 pandemic on the interest and loyalty of tourists traveling. The data were collected using a questionnaire with a Likert scale measurement scale. While the data analysis technique uses smart PLS. The results of this study suggested 1) there was a positive and significant direct effect between information exposure on visiting interest, 2) there was no positive nor significant direct effect between information exposure on tourist loyalty, 3) there was no positive nor significant direct influence between visiting interest on loyalty of tourists traveling, and 4) there was an indirect effect between exposure to information on loyalty through tourist interest as a mediating variable.